The ethical climate and its relation to individualised care - Vryonides, Stavros; Papastavrou, Evridiki (My University, 2019)
The achievement of the main goals of the nursing profession, including the provision of quality and individualised nursing care to patients, often requires improvements in the working environment of nurses, while there are various research evidences to support such a need. However, it is additionally recognised in the scientific community that the ethical climate of an organisation is actually an important component of the overall working environment that is related to employees’ shared perceptions of what is ethically correct behaviour and how ethical issues should be handled in organisations. Moreover, both the nurses’ practice environment and the ethical climate that exist in healthcare settings specifically, as it is perceived by nurses themselves, had been linked in some studies to various important professional variables and patient outcomes including individualised nursing care. Having this in mind, the aim of this chapter is to discuss the literature regarding the ethical climate as it is perceived by nurses themselves with a focus on the association between ethical climate and individualised nursing care. In this light the chapter attempts to demonstrate the existing body of relevant knowledge and the possible knowledge deficits that need exploration with further research studies.
Keywords: Ethical climate; Professional environment; Nurses; Individualised nursing care; Quality; Missed care